2009
DOI: 10.1016/j.virol.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of regions that can be crosslinked to RNA in the helicase-like domain of BaMV replicase

Abstract: The helicase-like domain of the Bamboo mosaic virus replicase catalyzes the release of 5'-gamma-phosphate from both ATP and 5'-triphosphated RNA by an identical set of catalytic residues with a presumably larger binding pocket for RNA. In this study, the peptidyl regions involved in RNA binding were mapped by reversible formaldehyde crosslinking and mass spectrometry. Eleven residues within these regions were examined by mutational analysis. H636A, Y704A, and K706A greatly diminished the enzymatic activities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The viral protein was expressed as inclusion bodies in E. coli BL21(DE3). To purify the viral protein, inclusion bodies were dissolved and refolded according to a protocol described previously (10). In detail, inclusion bodies were dissolved in protein buffer that contained 50 mM Tris (pH 7.5), 20 mM KCl, 0.1% Brij-35, 10% glycerol, and 10 mM ␤-mercaptoethanol supplemented with 8 M urea.…”
Section: Methodsmentioning
confidence: 99%
“…The viral protein was expressed as inclusion bodies in E. coli BL21(DE3). To purify the viral protein, inclusion bodies were dissolved and refolded according to a protocol described previously (10). In detail, inclusion bodies were dissolved in protein buffer that contained 50 mM Tris (pH 7.5), 20 mM KCl, 0.1% Brij-35, 10% glycerol, and 10 mM ␤-mercaptoethanol supplemented with 8 M urea.…”
Section: Methodsmentioning
confidence: 99%
“…The method for the cross‐linking of protein and biotinylated RNA by formaldehyde was based on a previous description (Han et al ., ). Formaldehyde is a reversible cross‐linking agent widely used in protein–DNA, protein–RNA and protein–protein interactions (Niranjanakumari et al ., ; Perez‐Romero and Imperiale, ; Sutherland et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, the greater value of K m (ATP) than K m (RNA) , which is about 2.5 fold, suggests that more active-site residues are involved in RNA binding. The peptidyl regions employed by the HLD to bind biotinylated RNA were mapped by the reversible formaldehyde crosslinking method followed by tandem mass spectrometry (Han et al, 2009). Five peptidyl regions were identified.…”
Section: Helicase-like Domain (Hld)mentioning
confidence: 99%
“…Compared with the well-characterized members in SF1, e.g., DNA helicase PcrA, the BaMV HLD seems to bind RNA using a different set of peptidyl regions. Mutagenesis of positively charged residues in these regions showed that some residues, e.g., K603 and R628, have a role in the virus movement (Han et al, 2009). …”
Section: Helicase-like Domain (Hld)mentioning
confidence: 99%